2010
DOI: 10.1007/s10552-010-9617-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the dietary guidelines for Americans and endometrial cancer risk

Abstract: The Healthy Eating Index (HEI) was developed by the US Department of Agriculture with the goal of quantifying adherence to the Dietary Guidelines for Americans. The purpose of this study was to evaluate the impact of the HEI-2005 score and each of its components on endometrial cancer risk in a population-based case-control study in New Jersey. A total of 424 cases and 398 controls completed a Food Frequency Questionnaire, which was used to derive the HEI-2005 score. Odds ratios (OR) and 95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…We have previously applied the DGAI 2005 to an Iranian population and the results have shown acceptable face validity [26,30]. Moreover, this index was associated with several participants’ characteristics and health outcomes, which is in line with the results of previous investigations using the DGAI, HEI, and Harnack scores [26,27,28,29,30,31,32,33,38,51,52,53,54,55]. Dietary scores are created on the basis of previous knowledge of a ‘healthy diet’ and are generally applicable to different ethnic groups [66,67,68].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…We have previously applied the DGAI 2005 to an Iranian population and the results have shown acceptable face validity [26,30]. Moreover, this index was associated with several participants’ characteristics and health outcomes, which is in line with the results of previous investigations using the DGAI, HEI, and Harnack scores [26,27,28,29,30,31,32,33,38,51,52,53,54,55]. Dietary scores are created on the basis of previous knowledge of a ‘healthy diet’ and are generally applicable to different ethnic groups [66,67,68].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, a decreased risk of colorectal cancer with increased Healthy Eating Index (HEI-2005) and USDA Food Guide Index scores [31,32,55] as well as a decreased breast cancer risk with closer adherence to the revised Diet Quality Index and Canadian HEI scores [38] have been observed previously. However, the studies of McCullough et al [52,53] and Chandran et al [33] have suggested only a limited value for HEI in predicting cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they address the biological interaction between nutrients and have relevance for interventions and dietary guidance. To date, only two small casecontrol studies and one prospective study have examined the association of diet quality and endometrial cancer; one using factor analysis found lower odds of endometrial cancer associated with a plant-based dietary pattern [5]; another found no association between the Healthy Eating Index-2005 score and endometrial cancer [6]; and another found no association between the Recommended Food Score and endometrial cancer [7]. The Women's Health Initiative (WHI) presents a key and unique opportunity to study this relationship prospectively among postmenopausal women, strengthen the scientific evidence base on diet quality and endometrial cancer, and inform the American Institute [14,15], alternate Mediterranean Diet (aMED) [16], and Dietary Approaches to Stop Hypertension (DASH) [17], are related to the risk of endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Accounting for all aspects of an individual’s diet as compared to assessing a single food group or nutrient could contribute to better understanding of a person’s nutritional lifestyle and consequent health benefits. In the past, dietary indices such as the Healthy Eating Index (HEI) have been utilized to assess the collective impact of a variety of foods and nutrients on endometrial cancer [17], breast cancer [18], and colorectal cancer risks [19, 20] as well as to predict major chronic disease risk [21, 22]. …”
Section: Introductionmentioning
confidence: 99%